The Impact of Sea Toll Program on Logistic Availability in Disadvantaged, Isolated, Outermost and Border Regions (T3p) in Indonesia - Mauritz H. M. Sibarani; Vidya Selasdini; Yosafat Anggiat Siregar (Dinasti International Journal of Education Management And Social Science, 2022)
Sea Toll is a concept of marine logistics transportation that aims to connect sea ports in the archipelago. Sea ports that are interconnected will be able to create smooth logistics transportation to isolated regions of the country. The government created a Sea Toll program to connect all islands in Indonesia and connectivity to Disadvantaged, Isolated, Outermost And Border Regions (T3P) In Indonesia to reduce price disparities in the eastern and western parts of Indonesia. This program has been running for almost five years, and has recorded achievements in the form of creating new connectivity in the Disadvantaged, Isolated, Outermost And Border Regions (T3P) as evidenced by the increasing number of ports of call. In addition, the distribution of logistics has increased, especially for basic necessities and essential goods, which is greater than in the previous period, as well as decreasing price disparities in several regions. This research is a type of research with quantitative methods. Data was collected by using a questionnaire distributed to 73 respondents that is employees of the Directorate of Sea Traffic and Transportation, employees of State-Owned Enterprises (BUMN) and private employees who cooperate in the implementation of the Sea Toll Program with a total of 20 statements. In looking for the results of calculations and data analysis, the author uses the SPSS version 26 program